Migration and Its Discontents: A Postcolonial Rendering of NoViolet Bulawayo’s We Need New Names - Mamadou Abdou Babou Ngom, P.D (International Journal of Advanced Science and Technology, 2020)
This research paper is my attempt, through a blow-by-blow analysis, to grapple with the manifold discontents that attend the event of migration. Using NoViolet Bulawayo’s We Need New names as a stepping-stone, I argue that migration, albeit a time-honoured phenomenon, has picked up speed in the twentieth-century into the twenty-first century with a most heavy human toll. The long-suffering postcolonial subject, hallmarked by the stifling strictures of marginality owing to a long history of race-based oppression that stretches back to the gruesome eras of the trans-Atlantic slave trade and colonization. I tap into key terms in postcolonial theory to emphasize the stultifying fallout from the migratory experience